THE THE TERATOGENIC EFFECTS OF ETHANOLIC EXTRACT OF BINTANGUR LEAVES (CALOPHYLLUM SOULATTRI BURM. F) ON FEMALE WHITE RATS - INARAH FAJRIATY; HAFRIZAL RIZA; FAJAR NUGRAHA; FRENGKI FRIANTO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Drugs can cause undesired effects on the fetus during pregnancy, especially embryonic/organogenesis which could lead to defects in the fetus because some types of drugs can penetrate the placenta and will undergo biotransformation into a highly reactive compound that has the potential to become a teratogenic compound. The aim of this research was to examine the teratogenic effect of bintangur leaves (Calophyllum soulattri Burm. F) ethanol extract to Sprague Dawley strain white rats. Methods: The white rats are divided into four treatment groups: Control group was given carboxymethyl cellulose Na 1%, comparison group was given trimethoprim 360 mg/kg BW, C. soulattri leaves ethanol extract (CLE) 100 mg/kg BW, and CLE 500 mg/kg BW. The treatment was administrated since organogenesis period. Cesarian section was performed to pregnant rat at the 20th day to separate the fetuses. Observation covered body weight of pregnant rats, fetal biometric, morphological malformation, and skeletal formation. Results: CLE 100 mg/kg BW and 500 mg/kg BW did not cause any change in the number of a living fetus, body weight, and length of fetuses like the comparison group. Both doses of CLE shown have a normal skeletal formation. Resorption was found in the comparison group and CLE 100 mg/kg BW with the percentage was 65.21% and 6.67%. It was found that there is no significant difference (p<0.05) between both doses of CLE compared to control group. Conclusion: From the results, it is concluded that CLE did not have the teratogenic effect.